Antiplatelet Drugs and Its Gastrointestinal Side Effects among Ischemic Stroke Patients in Dr. Hasan Sadikin General Hospital 2011 - Ananthakrishnan A/L Rajendram; Ike Rostikawati Husen; Andi Basuki (Althea Medical Journal, 2015)
Background: Antiplatelet drugs with known side effects are given in long term therapies to prevent secondary ischemic stroke. Gastrointestinal side effect is the most prevalent issue. The aim of this study was to identify which antiplatelet drugs have the most gastrointestinal side effects and the duration of administration. Methods: Seven hundred twenty six medical records were obtained from the Medical Record Department of Dr.Hasan Sadikin General Hospital Bandung from August to December 2011. Inclusion criteria were >18 years old and treated by long term antiplatelet drugs with complete medical records. Data analyzed descriptively consist of antiplatelet type, gastrointestinal effects, and drug administration duration. Results: Of 726 medical records only 246 were enrolled this study. Aspirin 80 mg was the most frequent drug given to ischemic stroke patients (65.9%). GI bleeding and nausea were the two side effects mostly found in aspirin >80 mg group (90%; 95% respectively). The side effects was found after less than 3 months in the aspirin >80 mg group, while it took longer to appear in clopidogrel 75 mg group. Conclusions: Aspirin (>80 mg) presents the most frequent gastrointestinal side effect compared to low dose aspirin 80 mg , clopidogrel, and combination of clopidogrel and aspirin.Keywords: Antiplatelet, ischemic stroke, side effects DOI: 10.15850/amj.v2n1.425